2021
DOI: 10.1146/annurev-environ-012220-012127
|View full text |Cite
|
Sign up to set email alerts
|

Locally Based, Regionally Manifested, and Globally Relevant: Indigenous and Local Knowledge, Values, and Practices for Nature

Abstract: The knowledge, values, and practices of Indigenous peoples and local communities offer ways to understand and better address social-environmental problems. The article reviews the state of the literature on this topic by focusing on six pathways by which Indigenous peoples and local communities engage with management of and relationships to nature. These are ( a) undertaking territorial management practices and customary governance, ( b) contributing to nature conservation and restoration efforts with regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 148 publications
3
60
0
1
Order By: Relevance
“…Conservation scientists who are also conservation practitioners are at the nexus of the twin spheres, and as such have both the greatest potential and responsibility to create positive change. We recognize that many individuals, organizations and groups are taking meaningful steps towards modes of conservation that empower BIPOC communities [1][2][3][4]59,60,77,78]. Nevertheless, there is still more to be done, and we must accelerate away from the exclusive and harmful institutions we have inherited, towards more inclusive and innovative institutions that promote conservation spaces in which people and nature thrive (figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation scientists who are also conservation practitioners are at the nexus of the twin spheres, and as such have both the greatest potential and responsibility to create positive change. We recognize that many individuals, organizations and groups are taking meaningful steps towards modes of conservation that empower BIPOC communities [1][2][3][4]59,60,77,78]. Nevertheless, there is still more to be done, and we must accelerate away from the exclusive and harmful institutions we have inherited, towards more inclusive and innovative institutions that promote conservation spaces in which people and nature thrive (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Diversify and broaden the curriculum; teach a more comprehensive representation of past and present conservation practice, including the work and perspectives of BIPOC scholars, and ultimately produce new 'standard' textbooks that encompass this history. Recommended reading [2,[59][60][61][62][63].…”
Section: Racism In Conservation Science and Practice Todaymentioning
confidence: 99%
“…Their current composition and structure are the result of intimate social-ecological interactions among Indigenous Peoples, plants, animals, and other non-humans (Balée, 2013;Fausto and Neves, 2018; Mendes dos Santos and Henriques Soares, 2021). These interactions are ongoing wherever Indigenous Peoples and other traditional communities have rights to their lands (Brondízio et al, 2021). It follows that conservation in these forest landscapes is not only about nature, as many conservationists imagine; it is about culture also.…”
Section: Rethinking Forest Conservationmentioning
confidence: 99%
“…Forests of high naturalness are variously termed intact forest landscapes, primary forests, pristine forests, and wilderness (Clement et al, 2020;Fletcher et al, 2021). Around the world, these forests are inhabited by Indigenous Peoples and local communities, who are co-responsible for the composition and conservation of their forests (Garnett et al, 2018;IPBES, 2019;Clement et al, 2020;Brondízio et al, 2021;Fernández-Llamazares et al, 2021), which makes all of the terms describing forests of high naturalness problematic. Worse, the people who inhabit these landscapes are seldom consulted by national governments or conservation organizations about forest conservation initiatives that affect their livelihoods (Clement et al, 2020;Brondízio et al, 2021;Fletcher et al, 2021), although numerous studies have shown that these people are responsible for the most preserved forested areas on Earth (Garnett et al, 2018;Fa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation